Intra-aortic Balloon Pump As a Bridge to Heart Transplant After Non-ST-Segment-Elevation Myocardial Infarction in Palliated Hypoplastic Left Heart Syndrome. (September 2019) - Osula, David; Farris, Gary Ross; Chatterjee, Arka; Law, Mark A.; Cribbs, Marc G.
Abstract : Supplemental Digital Content is available in the text.